The Influence of Profitability and Solvency Ratios on Stock Prices with Inflation as Moderating Variable (Case Study on BUMN) - Indrajaya, Danang (IJTB (International Journal of Technology And Business), 2019)
Abstract This study aims to examine the effect of Return on Assets (ROA), Return on Equity (ROE) and Debt to Equity Ratio (DER) on stock prices with inflation as a moderating variable in construction sector and basic industry companies which are listed on the Indonesia Stock Exchange during the period 2014-2018. This research is a quantitative study using multiple linear regression methods, t test and coefficient of determination test. Previously, the classical panel data assumption test which included normality test and multicollinearity test was conducted. Whereas the problem of heteroscedasticity and autocorrelation can be overcome by the Generalized Least Square (GLS) method. There are 8 SOE (state-owned enterprises)  construction and basic industry companies listed on the Indonesia Stock Exchange as research objects. The results of this study indicate that the Return on Assets (ROA) of several BUMN companies observed during the 2014-2018 period had a positive effect on their share prices, while the Return on Equity (ROE) and Debt to Equity Ratio (DER) of these companies had no effect significantly to the share prices. The results of this study also show that inflation does not moderate the ROA and DER relationship of several SOE companies which are observed to the share prices. On the other hand, inflation can weaken the effect of ROE on the share prices of several BUMN companies observed.   Keywords: ROA, ROE, DER, Inflation and Stock Prices.